Perceived determinants of food purchasing behavior applicable for behavioral change toward sustainable consumption - Pšurný, Michal; Baláková, Irena; Stávková, Jana; Langr, Alexandr (Frontiers in Sustainable Food Systems, 2024)
The paper deals with consumer behavior in the context of sustainable development of society. A questionnaire survey of 732 respondents was used to understand the determinants of food purchasing behavior toward sustainable consumption. The paper identifies the factors that the consumer determines in food purchasing as critical in terms of sustainable consumption and requiring behavioral change toward sustainability in terms of healthy lifestyle, reduction of food wastage, and conscious consumption. Respondents commented on 22 factors and the quantification of their impact on food waste and expressed the strength of opinion on sustainability issues. To evaluate the collected data, PCA factor analysis was used, which defines the importance of each factor by identifying artificial hypothetical variables, which are “Sustainability” and targeted education as appropriate tools for it, “Food usability,” which is a recommendation to producers by food quality, offering new types of food with longer shelf life, as well as “Pricing,” “Quality” and “Convenience.” The authors also sought to understand what measures they take in relation to waste and how they behave toward sustainable consumption and environmental protection. They created 14 content questions on this topic and by using factor analysis, 3 hypothetical variables were created, namely “Sustainable behavior” which expresses a healthy lifestyle, “Thoughtful purchase” which expresses a relationship with environmental protection before purchasing and “Zero waste” which means that the household tries to make additional use of food. Thus, it seeks a use for the food it cannot consume at a given time and creates a supply for other consumers. This behavior is a good prerequisite for achieving a change in consumption behavior. The influence of selected sociodemographic indicators on the frequency of wastage was also investigated using the χ-squared test. The influence of generation and number of children in the household on the frequency of wastage was demonstrated. The results of the analyses on the importance of individual factors and consumer behavior, especially of the young generation, argue for education on sustainable consumption.